Abnormal cerebral blood volume in regions of contused and normal appearing brain following traumatic brain injury using perfusion magnetic resonance imaging. - Garnett, MR; Blamire, A; Corkill, R; Rajagopalan, B; Young, J; Cadoux-Hudson, T; Styles, P (2001)
Following traumatic brain injury, there may be secondary alterations in cerebrovascular parameters leading to ischemia and further cellular damage. To assess possible subacute hemodynamic disturbances following traumatic brain injury, we used conventional and perfusion magnetic resonance imaging (MRI) in 18 patients, on average 10 days following injury. Six of the 18 patients had focal contusions or edema visible on conventional MRI. These six patients had a significantly reduced normalized regional cerebral blood volume (rCBV) in the regions of focal pathology compared to equivalent areas in control subjects (patients 0.47 +/- 0.20 [means +/- SD], controls 1.02 +/- 0.11, p < 0.001). In addition, four of these six patients had an increased rCBV (outside control range) in the region of normal appearing brain immediately surrounding the contusion. These six patients were more significantly injured and had a worse clinical outcome compared to the remaining patients (p = 0.004,p = 0.03, respectively). There were five patients who had a region of reduced rCBV (outside control range) in a quadrant of normal appearing white matter, away from any visible abnormality, who were not more significantly injured than the remaining patients but went on to have a significantly poorer clinical outcome (p = 0.27, p = 0.01, respectively). Traumatic brain injury is a heterogeneous insult causing a variety of pathology, not all of which is visible using conventional imaging methods. The current study has shown that regions of both normal appearing and contused brain may have an abnormal rCBV and that alterations in rCBV may play a role in determining the clinical outcome of patients.